Role of biofilm formation on the pathogenesis of Streptococcus agalactiae infection in red hybrid tilapia Oreochromis niloticus x Oreochromis mossambicus - Ibrahim, Isiaku Abdulsalam (2016)
Streptococcus agalactiae (group B Streptococcus, GBS) is an important pathogen of aquatic animals that has led to significant economic loss due to frequent disease outbreak and mortalities in fish worldwide. Tilapia has shown an unusual susceptibility to GBS infection, which is often characterised by acute septicaemia or chronic meningoencephalitis. While acute septicaemia is a sequel to an invasive infection, the mechanism of chronic meningoencephalitis in fish is not fully understood. However, most pathogens that induce acute invasive diseases are capable of developing biofilm associated chronic lesions. Biofilm is an assemblage of irreversibly attached microbial organisms within generated matrix of extracellular polymeric substances. The aim of this research was to investigate the role of biofilm in piscine GBS infection in red hybrid tilapia. A putative piscine GBS biofilm strain was selected and analysed for biofilm formation in vitro. The piscine GBS strain exhibited a weak attachment to polystyrene plates by standard crystal violet assay. Furthermore, fluorescent in situ hybridization and confocal laser scanning microscopy revealed discrete aggregates of attached piscine GBS around the brain meningeal surface of the orally exposed experimental tilapia. Importantly, these organised aggregates were first detected at a time point corresponding to the transition from an acute to chronic infection. The aggregates where embedded in a polysaccharide containing matrix and became intractable to antibiotic treatment despite earlier in vitro susceptibility on sensitivity test. The eye and stomach had no aggregates suggestive of the sessile life style. Intracellular bacterial aggregates, such as within erythrocytes and ventricular ependyma of the brain were also observed. Leukocytic infiltrates predominantly macrophages were readily seen around biofilms, while erythrocytes appeared often coagulated and severely injured as shown by increased expression of heat shock protein 70. Moreover, an effective adaptive immune response was not detected during the period of study. The erythrocytes may have facilitated invasion of GBS into the brain of tilapia. The present research demonstrates for the first time, that biofilm is associated with persistence of piscine GBS and development of chronic meningoencephalitis in the experimental tilapia. It provides a foundation for further investigation and the development of a holistic framework to prevent GBS infection in fish. Current approaches including vaccine strategies need to be reviewed to account for the biofilm phenotype.